Spectrophotometric study of the chromium(III)/azide system in the ultraviolet region and its analytical application - Lourenço, Leandro Maranghetti; Martins, Fernando Grine; Balbo, Valdir Roberto; Pimenta, Adriano César; Castro, Jorge Ricardo Moreira; de Andrade, José Fernando (Eclética Química, 2006)
A sensitive and alternative method for the spectrophotometric determination of chromium(III) based on the formation of chromium(III)/azide complexes was established by investigating a new band in the ultraviolet region. The best experimental conditions for the analytical determination of this metallic ion were: ligand and perchloric acid analytical concentration = 493 and 12.0 mmol L -1 , respectively; aqueous medium; T = 25.0 oC; contact time = 1 hour. The maximum molar absorptivity coefficient occurred at 287 nm (average 1.481 ± 0.008 × 10 4 L mol -1 cm -1 ), leading to the determination of metal ion concentrations one hundred times lower than the ones formerly determined in the visible region. The system obeys Beer’s Law and is suitable for chromium determination in the 0.702-2.81 mg L -1 concentration range (15-65% T, 1.00 cm-width quartz cells). Analytical applications of the current method were tested with a nutritional supplement containing chromium. Results were compared with those obtained with atomic absorption spectrometry.